2050: New Zealand's sustainable future. Issue 2 (16th March 2015) - Yeoman, Ian; Andrade, Amalina; Leguma, Elisante; Wolf, Natalie; Ezra, Peter; Tan, Rebecca; McMahon‐Beattie, Una
Abstract : Purpose: The purpose of this paper is to portray the future of tourism in New Zealand based upon a philosophy of sustainability and cultural identity as a response to the present 2025 Tourism Strategy. Design/methodology/approach: The research deployed a scenario planning methodology resulting in four portraits of the future. Findings: Environmental issues and global migration are the key issues that will shape the future of New Zealand tourism. In order to address these issues four scenarios were constructed. New Zealand Wonderland portrays a future based upon a grounded international reputation for environmentalism driven by good governance, climate change targets and ecotourism. Indiana Jones and the Search for Cultural Identity position a future driven by rapid growth and unregulated air travel resulting in environmental degradation. A Peaceful Mixture is a balance of socio‐cultural and environmental dimensions of sustainability at the centre of a tourism product shaped upon Maori culture and economic prosperity. The final scenario, New Zealand in Depression, is the worst possible outcome for New Zealand's tourism industry as the three dimensions of economy, community, and environment are not at equilibrium. New Zealand would be over‐polluted with an uncontrolled number of migrants. Research limitations/implications: The research was a social construction of ten experts' views on the future of sustainable tourism. Originality/value: New Zealand's present approach to the future of tourism is shaped by the 2025 Tourism Framework (http://tourism2025.org.nz/ ). This is derived from a business perspective and a neoliberal political philosophy and it is void of the words ecotourism and sustainability. This paper argues that the present strategy will fail because of community disengagement that proposes a range of alternative directions based upon a political discourse of sustainability and shaped by environmental credentials and cultural identity.